Histogram analysis of iodine maps from dual energy computed tomography for monitoring targeted therapy of melanoma patients. (February 2015) - Uhrig, Monika; Simons, David; Ganten, Maria-Katharina; Hassel, Jessica C; Schlemmer, Heinz-Peter
ABSTRACT : Aim: Iodine quantification with dual energy computed tomography (DECT) enables quantitative assessment of contrast medium uptake. Our purpose was to investigate patterns of enhancement under BRAF inhibitor therapy by performing histogram analyses (HAs) of iodine maps.Materials & methods: A total of 11 stage IV melanoma patients (32 metastases) underwent DECT at baseline and at least one follow up. Iodine uptake and HAs including maximum HU value (MAX), mean HU value (MEAN) and standard deviation (STD) was calculated.Results: For BRAF-responders MEAN, MAX and STD decreased significantly (p < 0.05). Nonresponder showed increasing MAX and STD for six out of seven lesions, while MEAN and Iodine uptake decreased (four) and increased (three).Conclusion: HA based on DECT enables a quantitative and functional criterion and contributes to accurate response assessment for promising targeted therapies.